Mediators of increased self-harm and suicidal ideation in sexual minority youth: a longitudinal study. Issue 15 (23rd November 2018) - Oginni, O. A.; Robinson, E. J.; Jones, A.; Rahman, Q.; Rimes, K. A.
Abstract: Background: Sexual minority youth have elevated suicidal ideation and self-harm compared with heterosexual young people; however, evidence for mediating mechanisms is predominantly cross-sectional. Using a longitudinal design, we investigated self-esteem and depressive symptoms as mediators of increased rates of suicidal ideation or self-harm (SISH) among sexual minority youth, and the roles of childhood gender nonconformity (CGN) and sex as moderators of these relationships. Method: In total, 4274 youth from the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort reported sexual orientation at age 15 years, and past-year SISH at age 20 years. Self-esteem and depressive symptoms were assessed at ages 17 and 18 years, respectively. CGN was measured at 30–57 months. Covariates included sociodemographic variables and earlier measures of mediator and outcome variables. Mediation pathways were assessed using structural equation modelling. Results: Sexual minority youth (almost 12% of the sample) were three times more likely than heterosexual youth to report past-year SISH (95% confidence interval 2.43–3.64) at 20 years. Two mediation pathways were identified: a single mediator pathway involving self-esteem and a multiple-mediated pathway involving self-esteem and depressive symptoms. Although CGN was associated with past-year SISH, it did not moderate any mediation pathways and there was no evidence for moderation by sex. Conclusions: Lower self-esteem and increased depressive symptoms partly explain the increased risk for later suicidal ideation and self-harm in sexual minority youth. Preventive strategies could include self-esteem-enhancing or protecting interventions, especially in female sexual minority youth, and treatment of depression.